2015
DOI: 10.1002/nbm.3429
|View full text |Cite
|
Sign up to set email alerts
|

Choline kinase-α protein and phosphatidylcholine but not phosphocholine are required for breast cancer cell survival

Abstract: High levels of total choline and phosphocholine (PC) are consistently observed in aggressive cancers. Choline kinase (Chk) catalyzes choline phosphorylation to produce PC in phosphatidylcholine (PtdCho) biosynthesis. PtdCho is the most abundant phospholipid in eukaryotic cell membranes and plays a dual role as the structural component of membranes and as a substrate to produce lipid second messengers such as phosphatidic acid and diacylglycerol. Chk-α, but not Chk-β, is overexpressed in various cancers, and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 49 publications
2
34
0
1
Order By: Relevance
“…It should be noted, however, that using a novel CHKA inhibitor, V-11–0711 [37], two independent laboratories have shown that drug-induced reductions of steady state PCho occurring after 24 h in HeLa and MDA-MB-231 were not sufficient to decrease cell viability, compared to CHKA RNAi [37, 38]; cell viability was lost only in SUM149 cells at similar drug concentrations. The groups infer that it is the depletion of CHKA protein - acting through non-catalytic functions [39] - but not inhibition of CHKA catalytic activity that is able to decrease cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that using a novel CHKA inhibitor, V-11–0711 [37], two independent laboratories have shown that drug-induced reductions of steady state PCho occurring after 24 h in HeLa and MDA-MB-231 were not sufficient to decrease cell viability, compared to CHKA RNAi [37, 38]; cell viability was lost only in SUM149 cells at similar drug concentrations. The groups infer that it is the depletion of CHKA protein - acting through non-catalytic functions [39] - but not inhibition of CHKA catalytic activity that is able to decrease cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…18 F and 11 C choline PET tracers are useful for identifying ChoK inhibition [28], but choline tracer accumulation can be affected by choline transport inhibitors [29, 30] which have known toxicities [31]. In addition, recent reports have shown that ChoKα protein scaffolding, rather than the enzymatic function, may be critical for supporting cell viability [21, 32, 33]. Miyake and Parsons reported a c-Src-dependent link between ChoKα and EGFR [32].…”
Section: Introductionmentioning
confidence: 99%
“…Miyake and Parsons reported a c-Src-dependent link between ChoKα and EGFR [32]. More recent studies showed that small molecule non- symmetric ChoKα inhibitors with low nM IC 50 s could substantially reduce the metabolic product PC but only cause reversible growth arrest with no effects on cell viability [21, 33]. Thus further development of fluorescence-based imaging strategies that report on enzyme expression rather than enzyme activity is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In a translational approach, we applied the CHKα-inhibitor V-11-0711 (Vertex Pharmaceuticals Incorporated) on GBM cells and tested subsequent alterations in geno- and phenotype. V-11-0711 has been shown to specifically suppress CHKα catalytic activity in breast cancer and HeLa cells [32, 33]. …”
Section: Resultsmentioning
confidence: 99%
“…Given our evidences from the genetic studies that CHKα controls mesenchymal differentiation, we tested the effect of compound based CHKα inhibition using the CHKα inhibitor V-11-0711 which recently has been shown to selectively inhibit CHKα activity [32, 33]. Analysis of metabolic extracts with 1 H NMR spectroscopy proved the enzyme inhibiting capability of V-11-0711 in GBM cells as we did not detect any CHKα product - PC at 3.22 ppm – after drug exposure (Figure 7).…”
Section: Discussionmentioning
confidence: 99%